The Effect Of Functional Endoscopic Sinus Surgery On Lung Function In Patients With Chronic Sinusitis And Nasal Polyps Without Asthma - Yıldırım, Metin; Belli, Seyda; Ozyilmaz, Cemal; Ogurlu, Ozcan (ENT Updates, 2018)
Objectives: The aim of this study was to look into how functional endoscopic sinus surgery (FESS) for CRSwNP without asthma affects lung function. The investigators aimed to determine any correlation between Lund-Kennedy scores, Lund-Mackay scores and pulmonary function. Methods: All participants underwent nasal endoscopic examination and CT scanning paranasally. Lund-Kennedy endoscopy and Lund-Mackay CT scores were calculated and compared with postoperative findings. Statistical analysis was performed to compare preoperative and postoperative spirometry findings to assess efficacy of surgery on pulmonary function. Results: There were no statistically significant differences between the Lund-Mackay scores for primary FESS and revision. Nevertheless, Lund-Kennedy scores did show evidence of greater statistical significance when comparing revision FESS and primary FESS (p=0.04) With respect to both primary and revision FESS patients there was no statistical significance between the preoperative values of FEV1, FEV1/FVC, FVC, and FEF25-75 and the same parameters measured one month postoperatively (p>0.05). Conclusion: Our results reveal that FVC improves following FESS in cases of CRSwNP that are not also asthmatic. No relationship was demonstrable between how severe the disease is and how the lung functions. Further research that looks at FESS in asymptomatic cases of airway obstruction over more prolonged follow-up needs to be undertaken.